Spatial distribution and composition of marine litter on sandy beaches along the Indian Ocean coastline in the south Java region, Indonesia - Yona, Defri; Nooraini, Pratiwi; Putri, Sisylia Eka Narriyah; Sari, Syarifah Hikmah Julinda; Lestariadi, Riski Agung; Amirudin, Akhmad (Frontiers in Marine Science, 2023)
Marine litter in coastal areas can bring economic, social, and environmental damage, especially the loss of aesthetic value of a tourist site. Therefore, research on the composition of marine litter to identify its sources is important for planning strategic action to minimize the problem. This study analyzed beach litter composition on five beaches (Kondangmerak, Balekambang, Ungapan, Ngudel, and Goa Cina) along the Indian Ocean coastline in the eastern part of the south Java region, Indonesia. All the beaches are known as the famous touristic beaches of Malang City, and receive many visitors, especially during the holiday season. Beach litter composition was obtained by collecting different types of litter in a 5 x 5 m square transect. Five square transects were placed along the beach strandline at each beach, and intervals of 20 m separated each transect. In each transect, the litter was collected and counted based on its category (plastic, paper, rubber, fabric, processed wood, metal, glass, ceramic, and hazardous items) and size (0.5–2.5cm, 2.5–5cm, 5–10 cm, and > 10 cm). There was a statistically significant variation in the number of litters among the sizes (p<0.05). However, the distribution of beach litter remained consistent across beaches regardless of its size. In general, beach litter with a size > 10 cm was found least on all beaches (< 15%), while the other three size categories were found in similar numbers (in the range of 20% to 50%). Plastic was the dominating type of litter on all beaches. Based on the Clean Coastal Index, all beaches were considered dirty to extremely dirty. All litter on the beaches was the product of tourism activities, and littering habits play a significant role as the source of marine litter in the study areas. Since this is the first study on the marine litter composition in the eastern part of south Java, the results of this study can be used as a baseline for future studies to prevent marine debris pollution and to develop management strategies for reducing the impact of marine debris on the environment.